KONSEP PEMBAHARUAN PEMIDANAAN DALAM RANCANGAN KUHP - A.A Ngurah Oka Yudistira Darmadi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
Criminal law reform in principle is an attempt to conduct a review and reestablishmentof law in accordance with the common values of socio-political, sociophilosophic,and cultural values of the people of Indonesia. Renewal of the CriminalCode criminal law angle can be done in two ways. First, the partial renewal, byreplacing part after part of the codification of the criminal law. Second, with therenewal of a general nature, thorough renewal by replacing total codification of thecriminal law. underlying purpose of a criminal law reform in Indonesia, including todetermine the political purposes to which a bill is nationally Indonesian State coversall aspects of society with keanegaragaman nation based on Pancasila. The draft penalcode reform set an another solution in addition to the imposition of imprisonment andhe organized an action against the perpetrators of criminal deprivation of liberty.